College Of Education Science Center Building - Rasha Yasin; Reem Abdat (My University, 2016)
The science centers building is a laboratory building  , which is located at An-Najah  National University in Nablus (new campus) . The aim of the establishment of this building is to providing additional laboratory specialties with high standard , which in turn will contribute in the prosperity of the university in the long term .   This project  , which is currently under construction consists of a two basement floors , ground floor , and top three floors ,with a total area of   6048.31m2   The first basement floor consists of electrical and mechanical room with an area of 1359.52m2.second basement floor consists a large  laboratory ,offices and library with an area of 957.03m2 .  Ground floor consists offices and training rooms with an area of952.93m2. In addition , the first floor has a laboratory ,offices and library with an area of 860.82m2 .Second and third floor  has a laboratory and offices with an area of 860.82m2  for each floor.   Structural models will be analyzed and designed by using computer software (SAP2000), and the results will be checked by hand calculations .In addition , AutoCAD will be used in drawing sections and details.                                                                                                                                  The Structural element will be designed as reinforced concrete members according to strength and serviceability criteria as specified in (ACI318-11), for seismic design UBC 97 will be used .

( ). .     m 26048.31     ( 1359.52)m2   (957.03) m2 952.57  860.82m2 . 860.82m2   (SAP2000) . .   (ACI318-11) UBC 97
College Of Education Science Center Building